The Effect of Post warming Culture Period Between Thawing and Transfer of Cryopreserved Embryos on Reproductive Outcomes After In Vitro Fertilization (IVF): A Systematic Review and Meta-analysis - LH Sordia-Hernandez; FA Martinez; EG Orozco; A Flores-Rodriguez; PC Leyva-Camacho; NA Alvarez-Villalobos; JA Zuñiga-Hernandez (JRI, 2021)
Background: The purpose of this study was to evaluate the effect of post warming culture period between thawing and transfer of cryopreserved embryos on reproduc-tive outcomes after in vitro fertilization (IVF). Methods: An extensive literature search was performed using PubMed, EmBase, and the Cochrane library from January 2000 to August 2019. A systematic review and meta–analysis of clinical trials was performed in this manuscript. The trials represented patients with embryo transfers of at least one previously cryopreserved good quality embryo. Main outcome measures of the study included clinical preg-nancy rate, live birth rate, miscarriage rate, and ectopic pregnancy rate.   Results: A total of 5338 trial/abstracts were identified through a literature search. Totally, five studies were included in the systematic review, and three in the final meta–analysis. The studies included 1717 embryo transfers, 605 after short culture, and 1112 after long culture. The clinical pregnancy rate (CPR) was the most con-sistent outcome reported. The CPR was slightly better after short time culture with a RR of 1.09 (0.95–1.26, 95%CI) but this difference was not statistically significant. The great heterogenicity in the results reported in the included studies made it impossible to compare all planned outcomes. Conclusion: There are no differences in reproductive outcomes if cryopreserved embryos are transferred after overnight culture or after two hours of culture follow-ing thawing. Due to small number and the poor quality of trials reported on this topic, the results of this review should be treated with caution.